Exploring Teacher-Student Rapport in Second Language Learning Classrooms: Challenges and Strategies (IUBAT Review, 2025)
This study explores the dynamics of teacher-student rapport in second language learning classrooms, focusing on the challenges and strategies that shape this critical relationship. Teacher-student rapport is pivotal in creating a supportive learning environment that fosters student engagement and motivation. However, building and maintaining this rapport in second language contexts presents unique challenges, including cultural differences, communication barriers, and varying student proficiency levels. This review synthesizes existing literature to identify common challenges faced by educators and the strategies they employ to overcome these obstacles. The findings reveal that successful rapport-building requires a combination of empathy, cultural sensitivity, and adaptive teaching methods. Moreover, the study highlights the importance of consistent and open communication, as well as the need for teachers to be attuned to the individual needs and backgrounds of their students. By understanding these factors, educators can better navigate the complexities of teacher-student interactions in second language learning settings, ultimately enhancing the learning experience.IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 223-242